Application of Roadmap DMAIC in the management of automotive line supply - Caixeta, Filipe Fernandes; Nunes, Deivid Marques; Santos, Aline Gonçalves dos (Brazilian Journal of Production Engineering, 2020)
In order for the production orders to be finalized, the balance must be transferred correctly between stock and line. In this context, pending production order problems due to balance discrepancies is a significant factor in increasing the lead time of the product. In this way, the general objective of this work was to improve the accuracy of the balance in the production line supply in an automotive company. For that, the methodology used was the DMAIC roadmap, developing the steps: define, measure, analyze, improve and control. It was defined that the area of ​​the administration of materials that has the most impact on the pending orders is the method of supplying by sequencing, in this way, the sequencing cell that showed greater process variability was selected. In the measurement period, there were 258 orders pending, by the cell with the greatest impact, representing approximately R 17,000.00 in men hours invested in analyzes of divergences. By analyzing the causes, to reduce pending order situations, it was proposed to make changes in the process flow, implement an information management framework and create a method of sequencing ID cards. After controlling the improvement, it was concluded that the occurrences of pending orders reduced. However, it is still necessary to increase the application of the improvements in every sequenced supply method, trying to further reduce the occurrences.